Pendaftaran Tanah Sistematis Lengkap Berbasis Partisipasi Masyarakat (PTSL-PM) di Kabupaten Bojonegoro - Fariz Wahyu Aditya; Sarjita Sarjita; Yendi Sufyandi (Sekolah Tinggi Pertanahan Nasional, 2020)
Abstract: The technical instruction number: 002/JUKNIS-300.UK.01.01/II/2019 dated on 1-02-2019 concerning Complete Systematic Land Registration Program Based on the Community Participation (Juknis PTSL-PM) enables the presence of community involvement as the manifestation of Article 42 paragraph (1) of the Regulation of the Ministry of Agrarian and Spatial Planning/Ka.BPN Number 6 of 2018. The practice can be found in Bojonegoro District which has started the PTSL–PM program before the issue of the technical instruction of PTSL-PM so that it causes issues related to the compatibility of the technical instruction of PTSL-PM implementation with the participative mechanism occurred in Bojonegoro District. The purpose of this research was to evaluate the implementation of the technical instruction of PTSL-PM. This research used qualitative research method through descriptive approach. The result of the research found that from 97 description of the activities as the comparison instrument, 48 activities were not appropriate, while 42 activities were appropriate (the activities type contains participation which is not regulated in the technical instruction of PTSL-PM) and 7 activities have not been studied so that those were not included in the research object. The components related to the working map, land data collection formation basic, and measurement method used were the components which affect the implementation of technical instruction of PTSL-PM the most. Land office of Bojonegoro District cannot perform the technical instruction of PTSL-PM fully since the participation method uniformity is not possible considering the community characteristic, human resource, and facilities-infrasturure which are different in each region.Keywords: PTSL, Community’s Participation, Technical Instruction Intisari: Petunjuk Teknis Nomor 002/JUKNIS-300.UK.01.01/II/2019 tentang Kegiatan PTSL Berbasis Partisipasi Masyarakat (Juknis PTSL-PM) memungkinkan adanya keterlibatan dari masyarakat sebagai perwujudan dari Pasal 42 ayat (1) Permen ATR/Ka.BPN Nomor 6 Tahun 2018. Praktiknya di Kabupaten Bojonegoro telah memulai program PTSL-PM sebelum diterbitkannya Juknis PTSL-PM sehingga menimbulkan persoalan terkait kesesuaian pelaksanaan Juknis PTSL-PM dengan mekanisme partisipatif yang telah terjadi di Kabupaten Bojonegoro. Tujuan penelitian ini adalah untuk mengevaluasi pelaksanaan Juknis PTSL-PM. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan deskriptif. Hasil dari penelitian ini adalah dari 97 uraian kegiatan sebagai instrumen pembanding, 48 kegiatan tidak sesuai, 42 kegiatan sesuai atau dapat disesuaikan (jenis kegiatan bersifat partisipasi namun tidak diatur dalam Juknis PTSL-PM) dan 7 kegiatan belum diteliti sehingga bukan merupakan objek penelitian. Komponen yang berkaitan dengan peta kerja, dasar pembentukan pengumpul data pertanahan dan metode pengukuran yang digunakan merupakan komponen yang paling mempengaruhi pelaksanaan Juknis PTSL-PM. Kantor Pertanahan Kabupaten Bojonegoro tidak dapat melaksanakan secara penuh Juknis PTSL-PM karena keseragaman metode partisipasi tidak dimungkinkan mengingat karakteristik masyarakat, sumberdaya manusia dan sarana prasarana memiliki perbedaan di setiap daerah.Kata Kunci: PTSL, Partisipasi Masyarakat, Petunjuk Teknis